Knowledge and vision of motives in literature (Journal of Oriental Studies, 2019)
Literature is a voice of history, an echo of takeoff and falling, and its appearance. Letters imprinted on the rock, leather or paper and words which sank into the soul are remembered and remained in mind, and are also constantly studied and comprehended in the most important data of mankind history. Motive is one of the most significant and important term, where it is necessary to pay attention at deep studying of literary works. “Motive” is a noble word which plays a large role as the alive representative of moral and world copulation in human life, representing the symbol of past, present and future on philosophy and psychology of regarding historical, political, social and other values. In order to keep in mind and remember, the mankind wrote down history, sang of eposes, and every time were inspired by motive of these works. For example, Magzhan Zhumabay in the poem named “Turkestan” revives forgotten history of the last centuries and describes lexemes, such as Turan, er turk, Turkestan, Afrasuab, kokzhal, fire. Motive Turan in the poem repeats 24 times, stimulating psychological motivation of the reader to provide awakening of their historical mind. These motives, which remind history and spiritual culture of Turan, play very important role in formation of the younger generation’s national consciousness. Key words: literature motive, Turan, er turk, Magzhan Zhumabay.